Serum Tumor Necrosis Alpha Response to aerobic Exercise Versus Added Sugar Elimination in Obese Sedentary Females - Aly, Zainab S.; Elalfy, Amr M.; Eletreby, Yasmine M.; Khedr, Mohamed E.; Saweres, Joseph W.; Abdelhady, Reem Hamdy; Elsafty, Rasha Galal; Yousef, Amera S. Aly; Aloraini, Saleh M.; Elagamy, Nevein N. (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: The transition of inflammatory response from short- to long-lived initiates a state of systemic low grade inflammation that breaks down the immune homeostasis leading to alterations all over the body, interrupting normal cellular physiology and raises most of non-communicable disease risks. Physical inactivity combined with obesity as the most common side effect, contributes greatly to the development of cardiovascular and arterial stiffening diseases on basis of aggravating inflammatory and oxidative stress responses. Both aerobic exercise and dietary sugar restriction are known interventions attempting to lower these risks counteracting for the disease progression through inhibiting the systemic low grade inflammatory state. Aims: To evaluate the effects of 8-weeks of aerobic exercise program and added sugar elimination on body’s inflammatory state in sedentary obese females aged 40–60 year. Methods and results: 60 participants were randomly assigned to one of three groups considering 20 for each: group I (aerobic exercise), group II (added sugar elimination), group III (aerobic exercise combined with added sugar elimination). TNF alpha levels and subject’s score on the inflammatory questionnaire were measured pre- and post-intervention. All groups showed significant improvement in TNF alpha levels and inflammatory questionnaire scores, with the combined group showing the greatest improvement (36.060%, 30.329% respectively). Conclusion: Both aerobic exercise and added sugar elimination independently or synergistically enhance the body’s anti-inflammatory mechanisms in sedentary obese females.